A Study on Pain and Hemodynamic Parameters in Minor Gynecological Procedures: Propofol – Fentanyl Vs. Ketamine – Midazolam - Sameer Najeeb, Dena; Halko Ahmed , Bnar (Diyala Journal of Medicine, 2022)
Background: One of the minor obstitrical procedures is dilation and curettage; pain usually occurs during it. Consequently, an anesthetic drug desires sufficient analgesia, brisk onset, and recovery. Objective: To evaluate two groups of drug combinations {midazolam 0.08mg/kg – ketamine (0.5mg/kg)} and propofol with (1mg/kg) –fentanyl dose (1mcg /kg)}, in hemodynamic parameters, pain scoring and recovery characteristics thus finding the optimal combination which can be applied all along the operation. Patients and Methods: It was taken100 patients weregoing through dilatation & curettage of approximately 15-30 min. Duration was enrolled after ethical committee approval in Erbil in 2022, and it was divided into two groups of 50 each. Baseline anesthesia was maintained, and the patients were haphazardly selected to get propofol 1mg/kg with 1 mcg/kg fentanyl (First group), midazolam 0.08mg/kg with 0.5 mg/kg ketamine (Second group) as a bolus to induce anesthesia and for maintenance. Then. pain scores, Aldrete scores, and hemodynamic signs were assessed during and after the procedure. Finally, the results were arranged and inspected statistically with the Student's unpaired t-test and chi-square test. Results: BP (systolic, diastolic) and PR were significantly higher in Group 2 compared with Group 1. No significant difference was found in the two groups regarding the parameters: the sedative level at 3-5 minutes (p = 0.499) and the duration of the operation (p = 0.105). Conclusion: group (propofol -fentanyl) was superior to group (midazolam–ketamine) and may be a good option in uterine dilation, and curettage (propofol –fentanyl) provides sufficient analgesia for the minor surgical intervention with accurate recovery characteristics like awakening time and response to verbal commands.